Understanding drivers and outcomes of lurking vs. posting engagement behaviours in social media-based brand communities. Issue 7 (3rd May 2020) - Fernandes, Teresa; Castro, Ana
ABSTRACT: Social media-based brand communities (SMBBC) are ideal tools to develop Consumer Engagement (CE). Yet, brands do not fully understand whether members are really loyally engaged with the brand and uncertainties remain regarding SMBBC return on investment. Therefore, our aim is to understand what drives CE within SMBBC, to relate it to different CE behaviours and to study its impact on brand loyalty. Data from 213 Facebook users was analysed using PLS-SEM. The study concludes that the drivers for passive/lurking and active/posting behaviours differ and vary according to brand type, with the former revealing a stronger positive association with brand loyalty than the latter. This study also provides valuable insights into CE literature and to brands holding SMBBC, helping them to successfully develop social media strategies.